1994
DOI: 10.3950/jibiinkoka.97.450
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatization of the petrous apex.

Abstract: Pneumatizationof the petrous apex was investigated in 226 subjects without middle ear disease by means of target imaging CT.The degree of pneumatization of all subjects was 32.7% (148/452 ears), but no difference in degree was revealed with distinction of bilateral ears or between sexes.In 148 ears with pneumatization of the petrous apex, a higher degree of pneumatization was found in larger mastoid cavities, suggesting that pneumatization of the petrous apex correlates with pnuematized air cells in other part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…9,10 In other studies, the pneumatization of the petrous apex was found positive in 32.7% of 226 subjects, and no difference in degree was revealed as far as both ears or genders were concerned; pneumatized air cells were more often found in the lower portions of the CT slices than in the higher ones. 11 Cerebrospinal fluid (CSF) rhinorrhea is a common complication after skull base surgery for cerebellopontine angle tumors. Petrous air cells are a potential route for CSF rhinorrhea and thus, CT assessment of these air cells is useful for preventing this complication.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 In other studies, the pneumatization of the petrous apex was found positive in 32.7% of 226 subjects, and no difference in degree was revealed as far as both ears or genders were concerned; pneumatized air cells were more often found in the lower portions of the CT slices than in the higher ones. 11 Cerebrospinal fluid (CSF) rhinorrhea is a common complication after skull base surgery for cerebellopontine angle tumors. Petrous air cells are a potential route for CSF rhinorrhea and thus, CT assessment of these air cells is useful for preventing this complication.…”
Section: Discussionmentioning
confidence: 99%